THE DESIGN AND APPLICATION OF COLORS OF SHAANXI SHADOW PUPPETRY IN TOURIST SOUVENIRS - Honghe, Gao; Yezhova, Olga Volodymyrivna (Theory and practice of design, 2025)
Abstract. This article focuses on the color system of Shaanxi shadow puppetry, analyzing its cultural connotation, design application and research status. The research uses means such as CorelDRAW software to extract the colors of shadow puppets and apply them to the design of cultural and creative products, verifying their value in evoking cultural memories and enhancing the competitiveness of products. Purpose. This research aims to interpret the symbolic meaning, functional roles and composition logic of the color system of Shaanxi shadow puppetry, apply its cultural symbols to product design, enhance the recognition and exchange value of the art form of Shaanxi shadow puppetry, and promote the creative transformation and innovative development of intangible cultural heritage. Methodology. By sorting out the research results covering various aspects such as the history, shapes, colors, tourism development and design applications of Shaanxi shadow puppetry, a theoretical foundation is laid for the research. Combining the application of Shaanxi shadow puppet colors in current related product designs, this paper explores the application strategies of the Shaanxi shadow puppet color system in cultural and creative products. With the help of color extraction plugins of professional software such as CorelDRAW, the colors of Shaanxi shadow puppetry were extracted and reconstructed, and applied to the design practice of cultural and creative products to verify the feasibility and effectiveness of the design strategy. Results. This research, through theoretical analysis and design practice, has confirmed that the color system of Shaanxi shadow puppetry has great potential in the design of cultural and creative products. By applying its traditional color semantics, cultural memory can be evoked, and the narrative and emotional connection of the product can be strengthened. Dynamic and three-dimensional design can integrate aesthetics and practical functions, enhancing market competitiveness. In the future, the application of technologies such as 3D printing and VR/AR can be explored to dig deep cultural narratives. The combination of traditional symbolism and modern design is of great significance for the protection, inheritance and modern application of intangible cultural heritage, which can transform Shaanxi shadow puppetry from cultural heritage to living practice. Scientific novelty. This study, based on an interdisciplinary research perspective, integrates theories from disciplines such as color semiotics and emotional psychology to conduct research on the application of colors in Shaanxi shadow puppetry in the design of cultural and creative products, providing a new perspective for the study of intangible cultural heritage. It also innovates design strategies, combines threedimensional color expression and other design strategies, breaks through traditional graphic design thinking, provides new methods for the design of cultural and creative products, and enriches the application forms of intangible cultural heritage colors in modern design. Practical relevance. This study integrates the colors of Shaanxi shadow puppetry into the design of cultural and creative products, which is conducive to inheriting and promoting the national intangible cultural heritage, and enables the ancient art to regain new vitality in contemporary society. It can provide reference for the design of cultural and creative products, help designers explore the color elements of traditional culture, and enhance the cultural added value and market competitiveness of products. By developing tourism souvenirs and cultural and creative products with regional characteristics, the integration of shadow puppetry and the tourism industry in Shaanxi can be promoted, and local economic development can be facilitated. Funding. This article was supported by the Project of Liaoning Province Social Science Planning Fund. (L22BXW017)